ZINC LEVELS IN HUMAN HAIR AND SERUM OF INFANTS AND CHILDREN AND THEIR RELATIONSHIP TO VARIOUS DISEASES IN THE UPPER EUPHRATES BASIN - OLCUCU, A; CAGLAR, P (Wiley-Liss, 1993)
The normal zinc levels in the serum and hair of healthy children within the age group of 0-15 years, in Elazig Province, the Upper Euphrates Basin, were determined. The relationship was investigated between various disease processes and the levels of zinc in the blood serum and hair of 92 children who applied with various complaints and were cared for at the pediatric clinics and services of the Elazig State Hospital and the Firat University Research Hospital. The hair and serum samples were analysed for zinc by flame AAS. For children with upper respiratory system and pulmonary complaints, no relationship was observed between zinc levels of hair or serum and their diseases. The zinc levels of hair and serum were lower in the children with infectious and communicable diseases or blood diseases than in the control group. (C) 1993 Wiley-Liss, Inc.
Keywords: TRACE ELEMENTS; HAIR ANALYSIS; BLOOD SERUM ANALYSIS; FLAME ATOMIC ABSORPTION